Validation of the emotional availability self-report for use with children 0-5 years - Scherbak, Veronica E., author; Dik, Bryan, advisor; Prince, Mark, committee member; Lucas-Thompson, Rachel, committee member; Merz, Emily, committee member (Colorado State University. Libraries, 2024)
Emotional availability (EA) is a relationship construct that is used to assess the health and quality of the relationship between a caregiver and their child by examining the contribution of each member of the relationship. Empirical research has found a great deal of evidence that EA is an important factor to consider in parent-child relationship research and is linked with various parental and child outcomes, such as mental health issues, and various child development issues, such as depression and personality disorders in mothers and children's development of theory of mind. Most of the extant research measures EA using an observational EA System (Biringen et al., 2014). However, in 2002, an Emotional-Availability - Self-Report (EA-SR) instrument was introduced to assess parental perceptions of EA in their relationship with their child (Biringen et al., 2002). Evidence for the validity of EA-SR scores has been established for use with children 0-18 months, but has yet to be investigated with older children. This study aimed to establish the reliability and validity of scores on the EA-SR for use with children 0-5 years of age. Data analysis included an Exploratory Factor Analysis (EFA) and a Confirmatory Factor Analysis (CFA) to determine the factor structure of the EA-SR, as well as an examination of convergent and discriminant correlations between EA-SR scores and those on other measures. Initial evidence was found that a 13-item short form of the EA-SR may be a valid and reliable measure of EA for children ages 3-5.
Keywords: emotional availability; parenting; validity; measurement; ages 0-5; self-report